PEMBERIAN PUPUK KASCING DAN URIN SAPI PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - yulia, Arnis En; Gusriyono, Fajar '; ', Sampurno ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT The research aimed to determine the effect of interaction giving of vermicompost fertilizer and cow urine to the growth of oil palm seeds (Elaeis guineensis Jacq.) and get a suitable combination for the growth of oil palm seedlings in main nursery. The research was conducted from April to July 2015. The research used to completely randomized design (CRD) factorial consisting of two factors . The first factor is vermicompost fertilizer consists of 4 levels: vermicompost fertilizer dose of 0 g/plant, vermicompost fertilizer dose of 25 g/plant, vermicompost fertilizer dose of 50 g/plant and vermicompost fertilizer dose of 75 g/plant. The second factor is the concentration of cow urine consists of 4 levels: cow urine concentrations of 0%, cow urine concentration of 20%, cow urine concentration of 30%/ and cow urine concentration of 40%. From two factors then obtained 16 combined treatment with 3 replications. Parameters measured were increase of seed high, increase of midrib number, increase of hump circumference, root volume, root crown ratio and dry seeds weight. The data were analyzed using ANOVA followed by Duncan further test at 5% level. The results of the research showed that application vermicompost fertilizer and cow urine on oil palm seed there is interaction between giving of vermicompost fertilizer and cow urine on increase of seed high and increase of hump circumference. Combination treatment of vermicompost fertilizer dose with 125 g/plant and cow urine concentration of 40 % showed the best results of all observed parameters.   Keywords: vermicompost fertilizer, cow urine, oil palm, main nursery